Analisis Pola Asuh Orang Tua Penderita Infeksi Cacingan Pada Anak Sekolah Dasar Negeri 004 Semangko Kecamatan Marang Kayu Kutai Kartanegara - Rosdiana, Rosdiana (Husada Mahakam, 2017)
SDN 004 Semangko Village, Marang Kayu District Kutai Kartanegara Regency is one of public elementary schoolsin Marangkayu sub-district. Based on the report of STP Puskesmas Marang Kayu Subdistrict, there were 26 cases ofworm infestation in 2014 (Pinworm), then in 2015 there were 36 cases (Pinworm, Pinworm, Ascaris Lumbricoides),while in 2016 were 33 cases (Pinworm , Tapeworm). Qualitative research methodology with case study approach.The purpose of research parenting parents that affect kecacinga. The results of research, parenting patterns ofchildren who are less worm less precise, either the affirmation of the rules, parental control of child hygiene orbalanced nutrition